2015
DOI: 10.1667/rr13758.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Radiation-Induced Genes with Noncancer Chronic Diseases in Mayak Workers Occupationally Exposed to Prolonged Radiation

Abstract: We examined the association of gene expression with noncancer chronic disease outcomes in Mayak nuclear weapons plant workers who were exposed to radiation due to their occupation. We conducted a cross-sectional study with selection based on radiation exposure status of Mayak plant workers living in Ozyorsk who were alive in 2011 and either exposed to: combined incorporated Plutonium-239 ((239)Pu) and external gamma-ray exposure (n = 82); external gamma-ray exposure alone (n = 18); or were unexposed (n = 50) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Interestingly, in previous work we had identified HNRPA1 and WNT3 as radiation-induced genes. HNRPA1 , belonging to the hnRNP-family, appeared to be involved in atherosclerotic processes in Mayak workers with internal plutonium exposure [24]. WNT3 was identified as a robust bioindicator that predicted more severe HARS in the first two days after exposure in baboons [12].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in previous work we had identified HNRPA1 and WNT3 as radiation-induced genes. HNRPA1 , belonging to the hnRNP-family, appeared to be involved in atherosclerotic processes in Mayak workers with internal plutonium exposure [24]. WNT3 was identified as a robust bioindicator that predicted more severe HARS in the first two days after exposure in baboons [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results presented here repeatedly showed the overrepresentation of microRNA-genes. Interestingly, deregulation of microRNA gene expression was noted in leukocytes of chronically radiation-exposed humans ( Abend et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve mRNAs and nine miRNAs were significantly associated with six different diseases, particularly those related to atherosclerotic processes. These associations were gender-and dose-dependent and 26 potential confounders were considered including age at exposure, age at biosampling, demographic, social habits, data related to health status [161]. Other studies found long-term changes in gene expression in medical workers [162,163], and in thyroid cancer tissue from patients exposed to Chernobyl fallout [164,165].…”
Section: Transcriptional Biomarkers Of Health Effectsmentioning
confidence: 99%